Minireview of Formation Damage Control through Nanotechnology Utilization at Fieldwork Conditions - Ngata, Mbega Ramadhani; Yang, Baolin; Aminu, Mohammed Dahiru; Emmanuely, Baraka Leonard; Said, Annasi Ayubu; Kalibwami, Daud Charles; Mwakipunda, Grant Charles; Ochilov, Elbek; Nyakilla, Edwin E (Energy & fuels, 2022)
Nanomaterials have been used in the oil and gas industry to improve thermal stability, rheology properties, and reactivity through fluid dispersion into the formation. Nanomaterials in producing wells can control formation damage near the wellbore regions. Foreign fluid invasion to the reservoir rock during drilling, fracturing, completion, enhanced oil recovery, and workover causes an interaction with the rock formation and fluids. This results in formation damage such as clay swelling and deflocculation, solid particle invasion, and asphaltene precipitation, all of which reduce production and lead to significant economic losses. In this review, we present the application of nanomaterials to oilfields as a way of optimizing production with minimal formation damage near the wellbore regions. Also, this review presents how the laboratory experiments from nanomaterials were upscaled to oilfields. The different types of nanomaterials used to control formation damage across producing fields around the world were investigated. This study has shown that nanomaterials are more effective than traditional materials to be used in oilfields for controlling formation damage during various stages of oil and gas development and it recommends that the effect of the relationship between nanoparticle size and type should be explored for effective application. However, because formation damage is caused for a variety of reasons, this work points out that many types of nanomaterials need to be combined to achieve multipurpose mitigation. Furthermore, more research concerning the dispersion of nanoparticles in cement slurry and fracturing fluid should be undertaken.